Answer:
f(x) = -2 (x + 2)² - 4
Step-by-step explanation:
f(x) = a (x - h)² + k (h , k) is vertex h = -2 k = -4
pass point (-1 , -6) f(x) = -6 and x = -1
-6 = a (-1 - (-2))² + (-4)
-6 = a - 4
a = -2
quadratic function: f(x) = -2 (x + 2)² - 4
Answer:
A.) the function is increasing on the interval (-∞, 0) and decreasing on interval (0,∞)
Step-by-step explanation:
Answer:
y = 1
x = -1
Step-by-step explanation:
x - 2y = -3, then x = 2y - 3
2x + y = -1
substitute for x:
2(2y - 3) + y = -1
4y - 6 + y = -1
5y = 5
y = 1
x = 2 - 3 = -1
So is 4 floors / 10 seconds
If you have 60 seconds you can multiple 10 by 6 because 10×6=60
so you also have to multiple 4 by 6
4×6=24
and because it's descending it's 100-24= 76
Answer:
$63
Step-by-step explanation:
The store is 20% off, Jessica has a coupon that is 5% off add that together and it's 25% off. $84 - 25% = $63